1995
DOI: 10.1002/path.1711750205
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression in normal, dysplastic, and neoplastic laryngeal epithelium. Absence of a correlation with prognostic factors

Abstract: p53 expression has been examined in 89 squamous cell carcinomas of the larynx (34 glottic, 28 supraglottic, 18 transglottic, 8 pyriform sinus, and 1 subglottic) obtained from 88 patients surgically treated in our centre. In addition, 59 laryngeal samples including normal respiratory epithelium and non-invasive squamous cell lesions were also tested. Frozen sections were immunostained with PAb 1801 and the results were correlated with pathological features, DNA ploidy and S-phase of the tumours, disease-free in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 23 publications
6
33
2
4
Order By: Relevance
“…However, there is no objecti ve evidence of a correlation between p53 expression and prognostic factors for head and neck carcinomas. 27 The absence of a correlation between the expression of p53 in the normal adjacent lTIUCOSa and in the tumor area of the same patients detected here agrees with literature data. Nees et £11.…”
Section: Allele Of Gene P53 Are ---------------------------------supporting
confidence: 92%
“…However, there is no objecti ve evidence of a correlation between p53 expression and prognostic factors for head and neck carcinomas. 27 The absence of a correlation between the expression of p53 in the normal adjacent lTIUCOSa and in the tumor area of the same patients detected here agrees with literature data. Nees et £11.…”
Section: Allele Of Gene P53 Are ---------------------------------supporting
confidence: 92%
“…The molecular alterations leading to the development and progression of these carcinomas remain unclear. Several genetic studies have identi®ed p53 gene mutations and protein overexpression as early events in the development of SCC of the upper respiratory tract and lung (Dolcetti et al, 1992;Nadal et al, 1995). Additionally, we and others have recently shown that deregulation of cyclin D1 by gene ampli®cation and overexpression is associated with advanced stages and poor prognostic evolution of laryngeal carcinomas (Jares et al, 1994;Meredith et al, 1995;Michalides et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…It is therefore under-standable that numerous studies have been devoted to the progression of OIN to invasive SCC. The role of cell-cycle proteins such as p16, p21, p27, p53, cyclin D1 and E have been extensively studied over the last two decades (Shin et al 1994;Fraczek et al 2007;Gorgoulis et al 1994;Gale et al 1997;Dolcetti et al 1992;Barbatis et al 1995;Nadal et al 1995;Poljak et al 1996;Uhlman et al 1996;Hirai et al 2003;Ioachim et al 2004;Wayne&Robinson 2006). However, none of these markers has been found to have reliable predictive value.…”
Section: Additional Markers Of Malignant Alterations Of Oral Intraepimentioning
confidence: 99%